2013
DOI: 10.1371/journal.pone.0058022
|View full text |Cite
|
Sign up to set email alerts
|

Essential Role of the Zinc Transporter ZIP9/SLC39A9 in Regulating the Activations of Akt and Erk in B-Cell Receptor Signaling Pathway in DT40 Cells

Abstract: The essential trace element zinc is important for all living organisms. Zinc functions not only as a nutritional factor, but also as a second messenger. However, the effects of intracellular zinc on the B cell-receptor (BCR) signaling pathway remain poorly understood. Here, we present data indicating that the increase in intracellular zinc level induced by ZIP9/SLC39A9 (a ZIP Zrt-/Irt-like protein) plays an important role in the activation of Akt and Erk in response to BCR activation. In DT40 cells, the enhanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
61
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 95 publications
(63 citation statements)
references
References 51 publications
2
61
0
Order By: Relevance
“…A family of zinc transporters (ZIPs), classified as fourteen isoforms, was identified (Grotz et al, 1998). ZIP9 and ZIP13 are expressed in the Golgi apparatus (Taniguchi et al, 2013), ZIP7 is expressed in the endoplasmic reticulum (Taylor et al, 2004), and the others are expressed in the cellular membrane (Fukada and Kambe, 2011). Since they are responsible for upregulating the concentration of zinc ions in the cytoplasm, ZIPs may be involved in the induction of MT expression via MTF-1 activation.…”
Section: Discussionmentioning
confidence: 99%
“…A family of zinc transporters (ZIPs), classified as fourteen isoforms, was identified (Grotz et al, 1998). ZIP9 and ZIP13 are expressed in the Golgi apparatus (Taniguchi et al, 2013), ZIP7 is expressed in the endoplasmic reticulum (Taylor et al, 2004), and the others are expressed in the cellular membrane (Fukada and Kambe, 2011). Since they are responsible for upregulating the concentration of zinc ions in the cytoplasm, ZIPs may be involved in the induction of MT expression via MTF-1 activation.…”
Section: Discussionmentioning
confidence: 99%
“…ZIP9 is localized to the Golgi apparatus and the cell surface (274,409). The Golgilocated ZIP9 plays a crucial role in B-cell receptor (BCR) signaling through regulation of Akt and ERK activity by translocating zinc from the Golgi lumen (397). The cell surface ZIP9 can function as a membrane androgen receptor and contributes to testosterone-induced prostate and breast cancer apoptosis through both zinc transporter functions and androgen signaling (25, 409).…”
Section: Zip9 (Zipi Subfamily)mentioning
confidence: 99%
“…Consistent with this, we found that in the absence of ZnT4, Akt expression was much lower in the lactating mammary gland. Accumulation of intracellular Zn decreases Akt expression (53), and the inability to mobilize Zn pools from the Golgi apparatus may also reduce Akt signaling (47). Whether reduced Akt expression in C57BL/6J lm/lm mice was a direct effect of dysregulated Zn homeostasis in the Golgi apparatus, global defects in Golgi organization and signaling scaffolds (35), ZnT2-mediated Zn accumulation into vesicles withholding Zn from activating Akt phosphorylation, or further alterations in cellular Zn homeostasis, is not currently understood.…”
Section: Ck8mentioning
confidence: 99%